A new species of Chrysobothris Eschscholtz feeding on Dudleya spp. (Crassulaceae) from California and Baja California, with biological, distributional and taxonomic notes on other North American Buprestidae (Coleoptera) - Westcott, Richard L. (Zootaxa, 2007)
Chrysobothris dudleyaphaga Westcott, new species, from California and Baja California is described and figured, and its biology is discussed in detail. It and a record for C. schaefferi Obenberger establish that larval and adult Buprestidae use hosts in the plant family Crassulaceae. Acmaeodera montezuma Obenberger and A. perforata Cazier are synonymized under A. consors Horn. The synonymy of A. auritincta Fall under A. delectabilis Waterhouse is reversed. New state records and other observations are provided for Xenomelanophila miranda (LeConte). Additional notes are provided for species in the genera Acmaeodera Eschscholtz, Agrilus Curtis, Anthaxia Eschscholtz, Brachys Dejean, Chrysobothris Eschscholtz, Phaenops Dejean, and Taphrocerus Solier.